Lipophilic statins in cognitively normal subjects: Associations with conversion to mild cognitive impairment in a long‐term longitudinal multi‐center study. (31st December 2021) - Padmanabham, Prasanna S; Liu, Stephen; Silverman, Daniel H
Abstract: Background: Studies of the relationship between the use of statins (HMG‐CoA reductase inhibitors) and subsequent cognitive performance have been variously reported to demonstrate beneficial, harmful, or no significant effects. We aimed to help clarify the relationship between statin use and long‐term trajectory in subjects cognitively normal at baseline, comparing users of statins with known moderate (atorvastatin) or high (simvastatin) lipophilicity and blood‐brain barrier penetrance (LS), to non‐users (nonS), or users of other statins (OS). Method: From a consecutive series of 2305 subjects enrolled in the Alzheimer's Disease Neuroimaging Initiative, 69 were excluded for taking combination statin drugs. Excluding statin users with less than 66 months of usage resulted in 340 CN subjects ( 189 nonS, 121 LS, and 30 OS) who were further studied. Subjects were stratified into groups with low (<175mg/dl), medium (175‐207mg/dl), or high ( ≥207mg/dl) baseline cholesterol levels. The significance of differential conversion rates was assessed by Chi‐Squared tests for homogeneity. Survival trajectories were created using the Kaplan‐Meier method, where an event was defined as conversion to mild cognitive impairment (MCI), and the significance of difference was assessed by the log‐rank test. Result: While serum cholesterol levels at baseline ranged widely (112‐174 mg/dl), among 112 subjects with low baseline cholesterol, levels did not significantly differ between those who did convert to MCI within 72 months (157 mg/dl) vs. those who did not (155 mg/dl), but their rates of conversion to MCI significantly differed according to LS use: 39.5% among LS vs. 14.8% among nonS+OS converted (p=0.025). The 6‐year event‐free survival of the nonS+OS group (88.7%; 95% CI 0.785‐1) and the LS group (64.0%; 95% CI 0.519‐0.789) also differed significantly (p=0.019). LS usage was associated with an increased absolute (+24.7%) and relative (+167%) risk. Conclusion: Lipophilic statin use was associated with more than double the risk of declining to MCI over 72 months of follow‐up in cognitively normal patients with low baseline cholesterol. In separate analyses, no such risk was observed among other statin users, nor among subjects with medium or high baseline cholesterol levels.